ChemInform Abstract: Crystal Growth Experiments in the Systems Ni2MSbO6 (M: Sc, In) Using Chemical Vapor Transport Reactions: Ni2InSbO6 and NiSb2O6 Crystals in the Millimeter Range. Issue 20 (20th May 2014) - Weil, M.; Mathieu, R.; Nordblad, P.; Ivanov, S. A.
Abstract Chemical vapor transport reaction of Ni2InSbO6 in the temperature gradient 1313 → 1233 K using HgCl2, HgBr2, PtCl2, or TeCl4 as transport agent leads to the growth of Ni2InSbO6 single crystals in the millimeter range.